Characterization and Antimicrobial Activity of Silver Nanoparticles Obtained by Green Synthesis from Cuminum cyminum (Cumin) - Kadriye Ozlem Saygi; Eftal Böke; Ramazan Erenler; Birgul Kacmaz; Aysun Ergene (Turkish Journal of Agriculture: Food Science and Technology, 2025)
The aim of this study was to synthesize silver nanoparticles (Ag@NPs) by green synthesis method using Cuminum cyminum (Cumin) plant extract. Green synthesis is preferred more than chemical and physical methods because it is a biological method in which nanoparticles are easily and rapidly obtained, as well as being environmentally friendly and cost-effective. The Ag@NPs obtained from the reaction were characterized by UV-visible spectrophotometer (UV-vis), Fourier-transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy and energy dispersive X-ray (SEM-EDX). Ag@NPs were found to have maximum absorbance in the range of 400-500 nm. Functional groups involved in the reduction of Ag@NPs were identified by FTIR analysis. The spherical appearance of Ag@NPs was determined by transmission electron microscopy. The antimicrobial effect of the synthesized AgNPs was tested on gram-positive and gram-negative bacteria using the minimum inhibitory concentration (MIC) method. The results show that Ag@NPs obtained from Cuminum cyminum (Cc) seeds have effective antimicrobial activity. The use of plant-derived materials is considered to be a promising strategy for the green synthesis of Ag@NPs and could be more widely used in the bio-medical field.